2017
DOI: 10.1016/j.eswa.2016.12.015
|View full text |Cite
|
Sign up to set email alerts
|

The effect of automated taxa identification errors on biological indices

Abstract: This is an electronic reprint of the original article. This reprint may differ from the original in pagination and typographic detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…However, most of the previous studies have focused on single-image data (see e.g. Ärje et al, 2010;Kiranyaz et al, 2011;Ärje et al, 2013;Joutsijoki et al, 2014;Uusitalo et al, 2016;Lee et al, 2016;Ärje et al, 2017) and have not taken the inherent hierarchical structure of the data into account. In single-image data studies, the posture of the specimens can have substantial impact on the classification.…”
Section: Ecological Assessmentmentioning
confidence: 99%

Human experts vs. machines in taxa recognition

Ärje,
Raitoharju,
Iosifidis
et al. 2017
Preprint
Self Cite
“…However, most of the previous studies have focused on single-image data (see e.g. Ärje et al, 2010;Kiranyaz et al, 2011;Ärje et al, 2013;Joutsijoki et al, 2014;Uusitalo et al, 2016;Lee et al, 2016;Ärje et al, 2017) and have not taken the inherent hierarchical structure of the data into account. In single-image data studies, the posture of the specimens can have substantial impact on the classification.…”
Section: Ecological Assessmentmentioning
confidence: 99%

Human experts vs. machines in taxa recognition

Ärje,
Raitoharju,
Iosifidis
et al. 2017
Preprint
Self Cite
“…They found a great discrepancy between the experts determining the true taxonomic classes and the audited laboratory workers. Contrastingly, in a study on the effect of mistakes made in automated taxa identification on biological indices, Ärje et al [2] found a relatively small impact. Literature on direct human versus machine comparisons in classification tasks in an aquatic biomonitoring context is equally scant and ambiguous.…”
Section: Sample Identificationmentioning
confidence: 89%
“…However, most of the previous studies have focused on single-image data [see e.g. 3,20,4,17,35,22,2] and have not taken the inherent hierarchical structure of the data into account. In single-image data studies, the posture of the specimens can have substantial impact on the classification.…”
Section: Sample Identificationmentioning
confidence: 99%
“…Moreover, these differences are not always evident even for a human expert [9,62,63]. In this sense, the accuracy of automatic classification results is critical to avoid affecting biological evaluation indices and to reduce the bias caused by automation in classification methods [59].…”
Section: Phase 1: Quantitative Analysis Of Retrieved Data and Assigne...mentioning
confidence: 99%
“…In some instances, SVM algorithms have been optimized based on class selection and splitting methods such as one-vs.-one, one-vs.-all [49], or half-against-half [54][55][56]. Likewise, Bayesian algorithms, including random forest (RF), random Bayes forest (RBF) [52], or random Bayes array (RBA), have allowed the application of class division, in some cases, regarding taxonomic information [57][58][59].…”
mentioning
confidence: 99%